Improving High School Adolescents Optimism Through a Best Possible Self Intervention - Rahman Pranovri Putra; Alnico Imam Nugroho; Anindhita Sasanti Rahajeng; Andi Fenita Aysila (Universitas Pendidikan Ganesha, 2024)
Adolescents will inevitably face challenges and obstacles in their educational journey, so an optimistic mindset is essential for positive problem-solving. The